EVALUASI KURIKULUM PELATIHAN PENYUSUNAN RENSTRA KEMENTERIAN ESDM BERDASARKAN KEBUTUHAN DAN HARAPAN ALUMNI PELATIHAN di PPSDMA - Helmi, Ahmad (JURNAL APARATUR, 2020)
The purpose of this study is to analyze the expectations and needs of training participants, to analyze the level of relationship of each expectation and need and formulation of improvements to improve the quality of the curriculum for the ESDM Ministry's Strategic Planning Training, and to formulate improvement  recommendations for the curriculum development of the ESDM Ministry's Strategic Planning Drafting Training. The research data was extracted with literature study techniques, questionnaires and interviews. Research informants are alumni of the ESDM Ministry's strategic planning training and Trainers of PPSDM Aparatur (curriculum experts and strategic training substance). Data analysis uses interactive model analysis. The results of this study are information on the expectations and needs of training participants, an analysis of the level of relationship of each expectation and needs of trainees in the ESDM Ministry's Strategic Planning and its improvements formula, andimprovement recommendations for curriculum development of the ESDM Ministry's Strategic Planning.